Sex differences in the neuroinflammatory signaling pathway: effect of miRNAs on fatty acid synthesis in microglia - Haolin Zheng; Akiko Mizokami; Sergio Romera-Giner; Jaime Llera-Oyola; Yosuke Yamawaki; Tomomi Sano; Eijiro Jimi; Francisco García-García; Takashi Kanematsu (Biology of Sex Differences)
Abstract Background Significant sex differences exist in the prevalence and incidence of Alzheimer’s disease (AD). Notably, testosterone has been reported to regulate cognitive functions in the brain, with low serum testosterone levels correlating with increased AD risk. However, the specific mechanisms underlying this relationship remain unclear. Recent studies have demonstrated that microglia, the primary innate immune cells in the brain, play a crucial role in AD development. Therefore, this study aimed to explore sex differences in microglial function, specifically focusing on the role of testosterone in miRNA-mediated regulation of microglial gene expression. Methods Microglia were isolated from pooled hippocampal tissue of five 8-month-old male and female mice. Total RNA was extracted and subjected to miRNA microarray analysis. The mouse microglial cell line MG6 was used for in vitro experiments. Following testosterone treatment, miRNA, gene, and protein expression levels were investigated. An inflammatory response was induced using lipopolysaccharide (LPS) stimulation, and subsequent p65 phosphorylation was assessed. Results Sex-dependent differences were observed in miRNA-mediated biological processes, with males exhibiting greater changes. Male-enriched miRNAs were associated with fatty acid synthesis and metabolism pathways. In MG6 cells, testosterone treatment upregulated the expression of several miRNAs enriched in male microglia, particularly those targeting genes related to fatty acid synthesis. Additionally, testosterone significantly reduced the gene expression of fatty acid synthase (FASN). This testosterone-induced inhibition of FASN expression attenuated NF-κB/p65 phosphorylation. Consequently, the suppression of FASN expression led to reduced expression and secretion of tumor necrosis factor-alpha following LPS stimulation in MG6 cells. Conclusions These findings suggest that testosterone modulates inflammation in male microglia by regulating fatty acid synthesis, potentially contributing to the observed sex differences in AD pathogenesis.